2017
DOI: 10.1111/evj.12691
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and pharmacodynamic effects of two omeprazole formulations on stomachpHand gastric ulcer scores

Abstract: ULS matched or slightly exceeded OMO plasma concentrations. Both products resulted in equivalent increases in gastric pH, gastric pH profiles and decrease in gastric ulcer scores. Thus, ULS was pharmacodynamically equivalent to OMO and was associated with an equivalent beneficial effect on gastric squamous mucosal ulceration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 24 publications
(34 reference statements)
1
34
0
Order By: Relevance
“…Endoscopic evaluation of the gastric mucosa was performed using a 3‐m endoscope (9 mm outer diameter, Olympus Medical Systems Corporation, Tokyo, Japan), as previously described, after insufflation of the stomach with air to permit complete visualization of the glandular and squamous gastric mucosa. Each horse's stomach was assessed using a validated equine scoring system with separate scores for the greater curvature, lesser curvature and fundus summed to give a squamous score, and separate scores similarly summed for fundic and pyloric glandular mucosa, as previously described . Gastroscopy examinations were video recorded and stored using a unique, randomly generated, 4‐digit identification number.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Endoscopic evaluation of the gastric mucosa was performed using a 3‐m endoscope (9 mm outer diameter, Olympus Medical Systems Corporation, Tokyo, Japan), as previously described, after insufflation of the stomach with air to permit complete visualization of the glandular and squamous gastric mucosa. Each horse's stomach was assessed using a validated equine scoring system with separate scores for the greater curvature, lesser curvature and fundus summed to give a squamous score, and separate scores similarly summed for fundic and pyloric glandular mucosa, as previously described . Gastroscopy examinations were video recorded and stored using a unique, randomly generated, 4‐digit identification number.…”
Section: Methodsmentioning
confidence: 99%
“…Gastric fluid was aspirated via the endoscope at the completion of mucosal scoring. Indwelling NGT were then placed by grasping a small piece of tape at the distal end of the NGT using endoscopic biopsy forceps and passing the 3‐m endoscope and NGT into the stomach, as previously described . GF (1‐10 mL) was aspirated every 2 hours via the NGT.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Squamous and glandular gastric ulceration were scored separately as previously described [31]. Briefly, a validated equine scoring system [32] was used in real time and on review of de-identified video-recordings to give separate scores for the squamous mucosa of the greater curvature, lesser curvature and fundus, which were then summed to give a squamous score; separate scores were similarly summed for fundic and pyloric glandular mucosa to give a glandular score.…”
Section: Gastroscopymentioning
confidence: 99%